Odpowiedzi

2010-04-10T15:52:50+02:00
2+(-6)=-4
-21 + 17=-4
-3 + (-8)=-11
7 + (-6) + 12 =13
15 + (-2) + (-11)=2
-8 + (-6) + (-3)=-17
7 + (-6)=1
18+ (-21)=-3
-7 + (-2)=-9
-17 +15=-2
-80 +12 =-68
24+(-51)=-27
-29 +(-28)=-57
-73 +17 =-54
3 5 3
2010-04-10T15:52:54+02:00
2+(-6)=-4
-21 + 17=-4
-3 + (-8)=-11
7 + (-6) + 12 =13
15 + (-2) + (-11)=2
-8 + (-6) + (-3)=-17
7 + (-6)=1
18+ (-21)=-3
-7 + (-2)=-9
-17 +15=-2
-80 +12 =-68
24+(-51)=-27
-29 +(-28)=-57
-73 +17 =-56
3 4 3
2010-04-10T15:53:21+02:00
2+(-6)=-4
-21 + 17=-4
-3 + (-8)=-11
7 + (-6) + 12 =13
15 + (-2) + (-11)=2
-8 + (-6) + (-3)=-17
7 + (-6)=1
18+ (-21)=--3
-7 + (-2)=-9
-17 +15=-2
-80 +12 =-68
24+(-51)=-27
-29 +(-28)=-57
-73 +17 =-56
1 5 1